Ergonomic intervention in fertilizer manufacturing company - Muhamad Aswadi Azmi (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The purpose of this study is to solve the ergonomic issues of lifting the fertilizer bag at Fertilizer Manufacturing Company. The study also use some ergonomics assessment tools to define and assess the problem occurred at bagging department due to manual lifting when transferring the bag onto the pallet. On site survey was conducted by using the Nordic Questionnaire during the visit to the company. The tools that were used to evaluate were Rapid Entire Body Assessment (REBA) and Workplace Ergonomic Risk Assessment (WERA).